2015
DOI: 10.1111/faf.12139
|View full text |Cite
|
Sign up to set email alerts
|

The proximate architecture for decision‐making in fish

Abstract: Evolution has since the very beginning resulted in organisms which can sort fitness-related information from noise, evaluate it and respond to it. In animals, the architecture for proximate control of behaviour and physiology has been gradually evolving since before the Cambrian explosion of animal phyla. It integrates many different survival circuits, for example for danger, feeding and reproduction, and operates through reflexes, instincts, homeostatic drives and precursors to human emotions. Although teleos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 187 publications
(377 reference statements)
0
29
0
Order By: Relevance
“…While the neural bases of these changes are presently unknown, environmental characteristics which lead to decision-making have been described thoroughly. For example, threat probability and distance vary in a continuum that restricts attention (Andersen et al, 2016), and therefore whether fast or slower responses are needed (Brown et al, 1999;Fanselow and Lester, 1988;Kavaliers and Choleris, 2001;Laundré et al, 2010;Mc-Naughton and Corr, 2004;Perusini and Fanselow, 2015). Thus, decision-making is biased towards escape (flight) or fight responses when the threat is proximal, while avoidance and freezing are elicited when threat is distal (Fanselow and Lester, 1988;McNaughton and Corr, 2004;Perusini and Fanselow, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the neural bases of these changes are presently unknown, environmental characteristics which lead to decision-making have been described thoroughly. For example, threat probability and distance vary in a continuum that restricts attention (Andersen et al, 2016), and therefore whether fast or slower responses are needed (Brown et al, 1999;Fanselow and Lester, 1988;Kavaliers and Choleris, 2001;Laundré et al, 2010;Mc-Naughton and Corr, 2004;Perusini and Fanselow, 2015). Thus, decision-making is biased towards escape (flight) or fight responses when the threat is proximal, while avoidance and freezing are elicited when threat is distal (Fanselow and Lester, 1988;McNaughton and Corr, 2004;Perusini and Fanselow, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In fish, defensive circuits have not been thoroughly described, but there is an increasing awareness that defensive behavior is a fundamental function in these animals (Andersen et al, 2016;Kalueff et al, 2012;Kittilsen, 2013). As a result, fish are increasingly being used in neurobehavioral research (Gerlai, 2014;Hall et al, 2014;Kalueff et al, 2014b;Stewart et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For passive gears, traps catch only a proportion of fish that come within a close proximity because some fish enter traps more readily than others (Diaz Pauli, Wiech, Heino, & Utne‐Palm, ; Thomsen, Humborstad, & Furevik, ). This could depend on a number of physiological factors, including physiological traits that underlie decision‐making and risk assessment (Andersen, Jørgensen, Eliassen, & Giske, ; Giske et al., ; Höglund et al., ; Øverli, Pottinger, Carrick, Øverli, & Winberg, ; Øverli, Winberg, & Pottinger, ; Winberg & Thörnqvist, ; Table ). For passive gears, it has been suggested that decision‐making after the initial gear encounter is a greater determinant of individual vulnerability to capture than encounter rate itself (Klefoth et al., ; Monk & Arlinghaus, ).…”
Section: The Capture Process and Selection On Physiological Traitsmentioning
confidence: 99%
“…The latter examples also underline the role of these circuits in regulating responses to stressful and aversive stimuli. Indeed, another layer that could be added to the overlap between SBN and the mesolimbic reward system is that of an "aversive behaviour network" (Misslin, 2003;Cezario et al, 2008;Panksepp, 2011;LeDoux, 2012a;Sternson, 2013;Canteras & Graeff, 2014;Andersen et al, 2016). This system is equivalent to the stress-anxiety-fear circuit.…”
Section: Stress and Sociality Network In The Vertebrate Brainmentioning
confidence: 99%